THE EFFECT OF EXPLOSIVE MUSCLE POWER IN THE ARMS AND LEGS ON FREE-THROW OUTCOMES IN BASKETBALL PLAYERS - Juharti Anggreni; J Jamaluddin; S Sahabuddin (International Journal of Basketball Studies, 2022)
The game of basketball is fast and requires a variety of balance and physical alignment, as well as very complex techniques. This study aims to determine the effect of the explosive power of the arm and leg muscles on the results of free throws in basketball players. The sample in this study were all male students who take part in basketball extracurricular activities of SMA Negeri 5 Soppeng, with a total of 30 students. The data analysis techniques used are descriptive analysis, data normality testing, data linearity testing, and regression analysis using the SPSS program. The findings revealed that, first, there was a 75.6% effect of explosive power of the arm muscles on the results of free throws in basketball games for Soppeng 5 Public High School students; second, there was a 77% effect of explosive power of the leg muscles on the results of free throws in basketball games for high school students Negeri 5 Soppeng; and third, there is an effect of explosive power of the arm muscles and explosive power of the leg muscles there was a 85,3%%. Further research needs to be done to obtain more optimal results when taking free throws. It is necessary to study other variables that can affect the results of free throws, such as mental conditions and other psychological aspects of basketball players when making free throws.